PENGARUH MEDIA PETA KEBERAGAMAN BUDAYA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN KELAS V MI SUMBERJAYA - Dewi Prasa; Neng Lia Yulianengsih (STKIP Subang, 2024)
This study aims to determine the extent of the influence of cultural diversity map media on students' learning outcomes in Civics Education (PKN) lessons. The subjects of the research were 31 fifth-grade elementary school students at MI Sumberjaya. In this study, three types of instruments were used to collect data: tests (pre-test and post-test), interviews with the classroom teacher, and documentation as evidence. The data collection techniques included tests, interviews, and observations. The results of the study showed that the use of cultural diversity map media had an impact on students' learning outcomes in PKN subjects. This is evidenced by the average cognitive ability scores of students in the pre-test, which was 45.81, being lower than the post-test score of 80.19. Additionally, the hypothesis test results using the paired sample t-test indicated a significant value (sig.) (2-tailed) of 0.000. According to the decision-making criteria in the paired sample t-test, a sig. (2-tailed) value < 0.05 or 0.000 < 0.05 indicates a significant influence of the cultural diversity map media on students' learning outcomes in PKN subjects.